2003
DOI: 10.1016/s0140-6736(03)13582-9
|View full text |Cite
|
Sign up to set email alerts
|

Personal exposure to nitrogen dioxide (NO2) and the severity of virus-induced asthma in children

Abstract: High exposure to NO2 in the week before the start of a respiratory viral infection, and at levels within current air quality standards, is associated with an increase in the severity of a resulting asthma exacerbation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
204
5
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 290 publications
(220 citation statements)
references
References 36 publications
8
204
5
3
Order By: Relevance
“…We found no link between pollutant concentrations and changes in lung function, similar to results of previous studies showing no clear association between indoor PM and lung function in few patients with COPD (27,28). NO 2 , a by-product of combustion with indoor sources including gas-burning appliances, may lead to worse respiratory health through airway epithelial damage, or lowering the threshold for viral-induced exacerbations (33,34). A cross-sectional study by Osman and coworkers (26) found no association between indoor NO 2 concentrations and worse quality of life in subjects with COPD.…”
Section: Discussionsupporting
confidence: 89%
“…We found no link between pollutant concentrations and changes in lung function, similar to results of previous studies showing no clear association between indoor PM and lung function in few patients with COPD (27,28). NO 2 , a by-product of combustion with indoor sources including gas-burning appliances, may lead to worse respiratory health through airway epithelial damage, or lowering the threshold for viral-induced exacerbations (33,34). A cross-sectional study by Osman and coworkers (26) found no association between indoor NO 2 concentrations and worse quality of life in subjects with COPD.…”
Section: Discussionsupporting
confidence: 89%
“…Viral and bacterial infections of the upper and lower respiratory tract can cause wheezing and can also influence the onset and severity of asthma. Viral infections are detected in 80-85% of asthma exacerbations in children [42] and 75-80% in adults [43,44]. Rhinoviruses are responsible for approximately 60% of the respiratory viral infections, whilst influenza, parainfluenza, respiratory syncytial virus, and adenovirus are responsible for the rest.…”
Section: Discussionmentioning
confidence: 99%
“…The continuous monitoring of tropospheric nitrogen dioxide (NO 2 ) is of great importance because it is one of the major pollutants that affects both humans and the biosphere directly and indirectly [1,2], and it plays an important role in tropospheric chemistry. Tropospheric NO 2 is one of six pollutants regulated by the US Environmental Protection Agency's (EPA) National Ambient Air Quality Standards, with the criteria set at 100 ppb for 1 h and 53 ppb for the annual average, according to the Clean Air Act (https://www.epa.gov/criteria-air-pollutants/naaqs-table).…”
Section: Introductionmentioning
confidence: 99%